Pemberdayaan Remaja Putus Sekolah Melalui Pelatihan Keterampilan Kerja - Lilis Irmawatie dan Joko Wigalih (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2012)
Adult phase denotes the productive, creative and potential age because teenagers are physically strong, high-spirited and their abilities still can be extended optimally. Adult period is also a transition which is quite vulnerable and susceptible to conflicts as a result of the adjustments of their living conditions. The existence of drop-out problems and unemployed teenagers in society rises recent conflicts that would intimidate the society. One of efforts of the government to solve these problems is through a social guidance program and work skills training including motorcycle mechanics and electronics skills training that implemented by The Sub Unit of Youth Development and Social Empowerment, Ciamis Regency for 4 months. This training aims to grow the independence of drop-out teenagers so that they are skilled and have high performance to unfold their quality of life. The given training had a result which apparently seen through their independence in opening a business, working, and possessing self-confidence, responsibility and interacting with their social environment.